2021
DOI: 10.18632/aging.202987
|View full text |Cite
|
Sign up to set email alerts
|

Plasma hemoglobin and the risk of death in HIV/AIDS patients treated with antiretroviral therapy

Abstract: Background: Previous studies concerning the effect of plasma hemoglobin (HB) and other factors that may modify the risk of death in people living with HIV/AIDS (PLHIV) treated with antiretroviral therapy (ART) are limited. Results: Higher HB was independently linked to a lower death risk in PLHIV, with a decrease of 29% (13%, 43%) per standard deviation (SD) increment after adjusting for CD4, VL and other potential factors [hazard ratio (HR): 0.71, 95% confidence interval (CI): 0.57-0.87, P<0.001]. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Therefore, the actual effect of anemia on the risk of death from PLWHA should be comprehensively assessed. Consistent with our results, two prior studies have reported that lower baseline plasma hemoglobin levels may be an independent marker of the risk of death in PLWHA ( 13 , 14 ). Another study indicated that anemia might be a predictor of AIDS-related mortality ( 23 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, the actual effect of anemia on the risk of death from PLWHA should be comprehensively assessed. Consistent with our results, two prior studies have reported that lower baseline plasma hemoglobin levels may be an independent marker of the risk of death in PLWHA ( 13 , 14 ). Another study indicated that anemia might be a predictor of AIDS-related mortality ( 23 ).…”
Section: Discussionsupporting
confidence: 93%
“…Although a series of previous studies have reported that plasma hemoglobin is associated with the health status of PLWHA, whether anemia plays an independent role in HIV/AIDS-related death remains unclear ( 13 16 ). This knowledge is valuable for the efficient prevention and control of HIV/AIDS in practice.…”
Section: Introductionmentioning
confidence: 99%
“…[ 14,15 ] Moreover, available studies have revealed the immune proliferation, senescence, exhaustion, and percentages of regulatory T cells (Tregs) may also reflect the immune recovery. [ 16,17 ] The nutritional status, [ 18 ] such as body mass index (BMI), [ 19 ] hemoglobin (HB), [ 20 ] and other parameters, [ 18 ] has been widely used for the assessment of prognosis of HIV‐infected patients, but their roles in the assessment of immune recovery are still controversial. The immune reconstitution is also linked to viral co‐infection (such as hepatitis B virus [HBV], [ 21 ] hepatitis C virus [HCV], [ 22,23 ] and syphilis, [ 24 ] ) and the specific ART protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive progression of HIV leads to decreased of immune response [ 8 ] as well as blood hemoglobin levels [ 9 ] and substantially associated with decreased survival of patients. This indicated CD4 cell count and hemoglobin level are the greatest biological markers in HIV patients and independent indicators of survival time to default from ART treatment.…”
Section: Introductionmentioning
confidence: 99%